Changes in the chikungunya virus E1 glycoprotein domain II and hinge influence E2 conformation, infectivity, and virus-receptor interactions - Thannickal, Sara A. (2024)
In a previous study to understand how the chikungunya virus (CHIKV) E1 glycoprotein β-strand c functions, we identified several attenuating variants at E1 residue V80 and the emergence of second-site mutations in the fusion loop (E1-M88L) and hinge region (E1-N20Y) with the V80 variants in vivo. The emergence of these mutations led us to question how changes in E1 may contribute to CHIKV infection at the molecular level. Here, we use molecular dynamics to understand how changes in the E1 glycoprotein may influence the CHIKV glycoprotein E1-E2 complex. We found that E1 domain II variants lead to E2 conformational changes, allowing us to hypothesize that emerging variants E1-M88L and E1-N20Y could also change E2 conformation and function. We characterized CHIKV E1-M88L and E1-N20Y in vitro and in vivo to understand how these regions of the E1 glycoprotein contribute to host-specific infection. We found that CHIKV E1-N20Y enhanced infectivity in mosquito cells, while the CHIKV E1-M88L variant enhanced infectivity in both BHK-21 and C6/36 cells and led to changes in viral cholesterol-dependence. Moreover, we found that E1-M88L and E1-N20Y changed E2 conformation, heparin binding, and interactions with the receptor Mxra8. Interestingly, the CHIKV E1-M88L variant increased replication in Mxra8-deficient mice compared to WT CHIKV, yet was attenuated in mouse fibroblasts, suggesting that residue E1-M88 may function in a cell-type-dependent entry. Taken together, these studies show that key residues in the CHIKV E1 domain II and hinge region function through changes in E1-E2 dynamics to facilitate cell- and host-dependent entry.IMPORTANCEArboviruses are significant global public health threats, and their continued emergence around the world highlights the need to understand how these viruses replicate at the molecular level. The alphavirus glycoproteins are critical for virus entry in mosquitoes and mammals, yet how these proteins function is not completely understood. Therefore, it is critical to dissect how distinct glycoprotein domains function in vitro and in vivo to address these gaps in our knowledge. Here, we show that changes in the CHIKV E1 domain II and hinge alter E2 conformations leading to changes in virus-receptor and -glycosaminoglycan interactions and cell-specific infection. These results highlight that adaptive changes in E1 can have a major effect on virus attachment and entry, furthering our knowledge of how alphaviruses infect mammals and insects.